HUMAN LANGUAGE AS NATURAL CODING: A PARADIGM SHIFT IN UNDERSTANDING SUMERIAN, ETRUSCAN, TURKIC, AND NATIVE AMERICAN LANGUAGES - Mahmudjon Kuchkarov; Marufjon Kuchkarov (World Scientific Research Journal, 2025)
This article introduces the Odam Tili (Human Language) theory, which proposes that human language evolved through natural coding mechanisms rooted in universal physiological, cognitive, and environmental factors. By examining phonetic and semantic parallels among Sumerian, Etruscan, Turkic, and Native American languages, the research challenges two foundational linguistic ideas: Ferdinand de Saussure’s principle of the arbitrariness of the linguistic sign and Noam Chomsky’s concept of universal grammar. The findings suggest that language is an adaptive, empirically grounded system shaped by shared human experiences, offering a new perspective for linguistics, anthropology, and cognitive science. This study calls for a paradigm shift in understanding language origins, emphasizing natural coding over abstract, innate structures.